2000
DOI: 10.1108/eum0000000005371
|View full text |Cite
|
Sign up to set email alerts
|

Organisational climate and corporate performance: an empirical investigation

Abstract: Interest in organisational climate and its link with corporate performance is gaining momentum. The aim of this paper is to contribute to this discourse by examining the extent to which “above” and “below” average performing companies also exhibit different climate measurements. A survey was conducted on a sample of electronic component manufacturers, as a sunrise industry in a growth phase, and hosiery and knitwear manufacturers, as a sunset industry, in decline. In turn, sub‐samples of companies that perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
10

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 27 publications
(32 reference statements)
3
29
0
10
Order By: Relevance
“…Research conducted in forensic mental health settings has often focussed on the connection between social climate and treatment outcomes; in other words, how the perception of the social environment impacts upon patient care (Clarke et al 2002a;Gelade & Ivery 2003;Griffin et al 2010;Kangis et al 2000;Langdon et al 2004;Langdon et al 2006;Moos & Bromet 1978;Pritchard & Karasick 1973). One study by Arnetz and Arnetz (2001) found that fear of violence experienced by health care staff was negatively and significantly related to patientreported quality of care.…”
Section: Correlates Of Social Climatementioning
confidence: 99%
“…Research conducted in forensic mental health settings has often focussed on the connection between social climate and treatment outcomes; in other words, how the perception of the social environment impacts upon patient care (Clarke et al 2002a;Gelade & Ivery 2003;Griffin et al 2010;Kangis et al 2000;Langdon et al 2004;Langdon et al 2006;Moos & Bromet 1978;Pritchard & Karasick 1973). One study by Arnetz and Arnetz (2001) found that fear of violence experienced by health care staff was negatively and significantly related to patientreported quality of care.…”
Section: Correlates Of Social Climatementioning
confidence: 99%
“…El desempeño tuvo una mayor asociación con la dimensión de identidad, luego recompensa, apoyo, calidez, normas, conflicto, estructura y riesgo. Cabe destacar que los son congruentes con otros estudios en que se ha mostrado una relación entre el clima y desempeño, desde Forehand y Gilmer en 1964, hasta estudios más actuales (Kangis & Williams, 2000;Fey & Beamish, 2001;Burton & Lauridsen, 2004;Griffith, 2006). Además los resultados concuerdan con los meta-análisis realizados por Schratz (1993), donde se menciona que dimensiones de clima como, apoyo, riesgo y decisiones, recompensas, relaciones entre compañeros y estructura se han asociado históricamente con desempeños y resultados organizacionales.…”
Section: Discussionunclassified
“…Tradicionalmente ha sido relacionado con dimensiones financieras, con el posicionamiento y adaptación a los cambios en el mercado, con los márgenes promedios de ganancia organizacional, con el rendimiento en base al capital empleado, con el crecimiento en las ventas, etc. (Kangis & Williams, 2000). Asimismo, hay quienes lo consideran en base a metas logradas y recursos que se utilizan para lograrlas (De Juan, 2004), y quienes centran la atención en la inestabilidad económica (Fey & Beamish, 2001).…”
Section: Clima Satisfacción Laboral Y Desempeño: Algunas Clarificaciunclassified
“…Success comes from having strategy become everyone's everyday job." To this point, there is increasing research on the importance of company-internal variables for explaining performance (Kangis and Williams, 2000). Kaplan and Norton (2004) even label intangible assets as the ultimate source of sustainable value creation.…”
Section: Valuing Strategy As An (Intangible) Assetmentioning
confidence: 99%
“…In spite of the rapidly rising importance of the internet as a platform for disclosure, the main literature on disclosure pays little attention for disclosure through press releases or websites.. As for ranking corporate disclosure on the internet of large Dutch companies, pioneering work has been delivered by Dutch leading financial daily newspaper "Het jeopardize a firm's strategic performance (Barney, 1986) and short enough not to permit long-term economic climates and cycles to influence the results (Kangis and Williams, 2000).…”
Section: Disclosure Through Websitesmentioning
confidence: 99%